Respostas
respondido por:
1
f(x)=x²+3x+2
É só substituir os valores de f na função acima.
A) f(1) = 1²-3×1+2
f(1) = 1-3+2
f(1) = 0
B) f(2) - f(3)
f(2)= 2²-3×2+2
f(2)=4-6+2= 0
f(3)= 3²-3×3+2= 2
0-(+2) = -2
C) f(4) = 4²-3×4+2
= 16-14= 2
f(4)-f(1)+f(2)= 2-0+0=2
É só substituir os valores de f na função acima.
A) f(1) = 1²-3×1+2
f(1) = 1-3+2
f(1) = 0
B) f(2) - f(3)
f(2)= 2²-3×2+2
f(2)=4-6+2= 0
f(3)= 3²-3×3+2= 2
0-(+2) = -2
C) f(4) = 4²-3×4+2
= 16-14= 2
f(4)-f(1)+f(2)= 2-0+0=2
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás